EFFECT OF PLANT GROWTH REGULATOR CONCENTRATION AGAINST THE GROWTH OF CROWN SHOOT OF THE PINEAPPLE ON PEAT LAND - Gustami Gustami; Warganda Warganda; Agustina Listiawati (Jurnal Sains Pertanian Equator, 2019)
ABSTARACTEfforts to multiply pineapple plants to date have not been many that use buds that come from the crown (Crown), seeds that come from this crown can produce more than one bud. the crown require hormones for optimal growth, one of which is by using superior plant hormones that play a role in stimulating the growth of pineapple seeds from the crown. The aim of this study was to find the best concentration of ZPT for the growth of pineapple seedlings from the crown on peat land. This research was carried out in a farm owned by a farmer, Jl. Parit Haji Mukhsin 2, with a study period of 3 months starting from 15 2018 January to 15 April 2018. The design used in this study was a Randomized Block Design (RBD) with 6 levels of ghost hormone treatment and each treatment there were 4 replications, each replication there were 3 samples. The treatment in question is h0 = without giving superior plant hormones, h1 = superior plant hormone concentration 3 ml / l, h2 = 5 ml / l superior plant hormone concentration, h3 = 7 ml / l superior plant hormone concentration, h4 = plant hormone concentration 9 ml / l superiority, and h5 = 11 ml / l superior plant hormone concentration. The variables observed in this study were height increase in plants, increase in the number of leaves, chlorophyll leaves, dry leaves and leaf area. The administration of superior plant hormones 11 ml / l can to increase the growth of the variable number of leaves and dry weight of the plant.Keywords:Black Plant Hormone, Peat Land, Pineapple